BEYOND ENTERTAINMENT: INNOVATING E-COMMERCE WITH TIKTOK SHOPPING AND ITS IMPACT ON GEN Z CONSUMERS’ BEHAVIOR IN MALAYSIA - Wan Mohamad, Wan Maisara; Kimpah, Jeniboy; Rakiman, Umol Syamsyul; Sa’adin, Izmayani; Masri, Hanis Marhaini; Abdullah, Hasnida (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
The integration of social media and e-commerce has transformed consumer behavior, with platforms like TikTok playing a pivotal role in shaping new online shopping experiences. This research explores the innovative role of TikTok's shopping features in influencing the consumer engagement and purchasing behaviors of Generation Z in Malaysia. Known for their digital fluency and preference for interactive content, Gen Z represents a key demographic in the social commerce revolution. Despite TikTok's growing presence in the region, limited research exists on how the platform's unique algorithm, user interface, and personalized shopping features influence consumer decisions, particularly in Malaysia. This study adopts a quantitative research method, utilizing a structured questionnaire to gather data from Gen Z users in Malaysia. The research focuses on the ease of use of TikTok’s shopping features, the influence of influencer marketing, and the integration of social and commercial content. The results indicate that while TikTok’s personalized and interactive features foster high levels of engagement, the conversion from engagement to purchase remains suboptimal. Key factors such as user interface design, trust in influencers, and the seamless blending of entertainment and commerce play significant roles in shaping Gen Z’s purchasing behavior. The findings provide valuable insights for marketers and businesses looking to optimize TikTok as a platform for social commerce. By understanding how TikTok’s features influence user engagement and purchasing decisions, brands can tailor their strategies to create more authentic, engaging shopping experiences that resonate with Malaysia’s Gen Z demographic. This study contributes to the growing body of knowledge on social commerce, offering practical recommendations for leveraging TikTok's innovative features to enhance e-commerce outcomes.